1993
DOI: 10.1080/15324989309381375
|View full text |Cite
|
Sign up to set email alerts
|

Cottage cheese (acid) whey effects on sodic soil aggregate stability

Abstract: Whey applications reduce a sodic soil's exchangeable sodium percentage (ESP) and sodium adsorption ratio (SAR) and increase its infiltration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…The stability of macropores, as well as aggregates, influences soil hydraulic properties (Murphy et al, 1993). Lehrsch et al (1994) found the percentage of stable aggregates in largely undisturbed soil to drop from 64 to 46 as acid whey applications to a silt loam soil in southern Idaho increased from 500 to 1000 t/ha. In a similar manner, at the greater water suction of 150 mm, infiltration into the bottoms of treated furrows again decreased uniformly as whey was applied (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The stability of macropores, as well as aggregates, influences soil hydraulic properties (Murphy et al, 1993). Lehrsch et al (1994) found the percentage of stable aggregates in largely undisturbed soil to drop from 64 to 46 as acid whey applications to a silt loam soil in southern Idaho increased from 500 to 1000 t/ha. In a similar manner, at the greater water suction of 150 mm, infiltration into the bottoms of treated furrows again decreased uniformly as whey was applied (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To satisfy the wheat's transpiration demand, we used a solid-set sprinkler system to apply 65 ± 16 mm (mean ± S.D.) of water in 24 h on 25 May and, from 30 June to 1 July, 76 ± 14 mm in 28 h. This water commonly has a pH of 8.2, an EC of 0.5 dS/m, and an SAR of 0.65 (Lehrsch et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations